The effect of work locus of control and general health on accident - proneness : The mediator role of effort - reward imbalance - behnam moradi; Amir Barkhordari; akbar Barkhordari; hamzeh gheysvandi; mahshid asgari (Shahid Sadoughi University of Medical Sciences, 2020)
Introduction: Workers' accident-proneness is considered as an inherent and coherent feature in incidence of occupational accidents. Therefore, recognizing its determinants could be effective in preventing such accidents. This study aimed to investigate the effect of work locus of control and general health on accident-proneness with the regard to the mediating role of effort-reward imbalance. Methods: This analytical and cross-sectional research was conducted in 2018 using structural equation modeling (SEM) with partial least square approach. In total, 225 employees with a history of occupational accidents in  Esfahan Steel Company were selected. Data analysis was performed using SPSS-23 and SMARTPLS3. Results: The obtained results indicated that the measurement and structural models were fitted. In addition, results demonstrated that all assumptions of the research were significant with the exception of the general health effect on accident proneness.  Conclusion: The results of this study showed that by controlling the work environment stressors, such as balancing effort-reward, could reduce the  accident- proneness. In addition, by checking the general health and work locus of control  to prevent the occupational accidents in the sieving process, people with internal control should be selected for stressful occupations.